PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS I SDN 006 TRI MULYA JAYA - Tukirah Kurniasih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low student learning outcomes IPA. Of the 20 studentswho completed only 9 students and the average student learning outcomes of 62. The resultsof student learning is still below the specified KKM is 65. The purpose of this research is toimprove the learning outcomes of the first grade science students at SDN 006 Tri Mulya Jaya.This research is a class act, carried out by two cycles. This research was conducted byapplying direct instructional model. The data used in this research is data teacher andstudent activities and student learning outcomes IPA. Research suggests that the applicationof the model pembelajara direct positive impact, namely by increasing the activity data andthe results of teachers and students learn science. In the first cycle of the first meeting activityfor teachers to get a percentage of 37.00%, in the first cycle II meeting increased with thepercentage of 50.00%, in the first meeting silus II teacher activity increased with thepercentage of 74.00% and the second cycle of meeting II increases with the percentage of82.00%. Besides the student activity also increased, in the first cycle of meetings I earn apercentage of 37.00%, in the first cycle II meeting increased with the percentage of 41.00%,in the first meeting silus II student activity increased with the percentage of 76.00 % and thesecond cycle II meeting increased with a percentage of 80.00%. IPA learning outcomes ofstudents also increased in the first cycle the number of students who completed study resultsberjuumlah 14 (70.00%), and the second cycle the number of students who have increased thenumber of students 17 (85.00%). Similarly, the average value obtained in the classical studentat baseline was only 62, and after the first cycle increased by an average of 72.5 after thesecond cycle is increased to an average of 76.5.